GaAsing up cellphones. - Goldstein, H.
A group of researchers from the Texas-based company, Freescale Semiconductor Inc., has fabricated metal oxide semiconductor field-effect transistors (MOSFET) using gallium arsenide and a novel gate dielectric. If the group can overcome some significant manufacturing challenges, this innovation could lead to a cellphone-on-a-chip and instant analog-to-digital conversion. It may even enable chip makers to improve processor speed and performance when transistors on silicon chips can be miniaturized no further.
Keywords: Freescale Semiconductor Inc; MOSFET; Analog-to-digital conversion; Cellphone-on-a-chip.; Gallium arsenide; Gate dielectric; Metal oxide semiconductor field-effect transistors; Multimedia handsets